The Dilemma of Maternity between Need and Duty: A Feminist Reading of Doris Lessing's the Fifth Child - Helaly Khalaf, Mohamed Fathi (International Journal of Criminology and Sociology, 2022)
Doris Lessing is widely known as one of the most celebrated contemporary female writers in English literature. Unlike other feminist writers who advocate equality between women and men, Lessing’s feminism is mainly concerned with defending women in the context of the different social pressures they are exposed to in a given society. The Fifth Child is one of Lessing novels in which she adopts the implicit feminist approach in portraying the character of Harriet Lovatt. Harriet Lovatt wants to lead a free life disregarding the conventions of marriage and maternal life in the sixties by getting married to David and having a large family. Therefore, she is scapegoated by her society for deviating from the prevailing norms. The main aim of the study is to analyze The Dilemma of Maternity between need and obligation, based on the Feminist Reading of Doris Lessing's the Fifth Child. The study demonstrates that how Harriet has to adapt to her adverse situation and, in doing so, she has to overcome a lot of hardships in the process of constructing a new self. In a word, Lessing wants to underscore how the condition of any woman who wants to live on her own is worsened just because of deviating from the prevailing norms in her community. Moreover, in this study, we attempt to point out the maternity dilemma in today’s society, and finally, draw some conclusion.